Intestinal outcome of bone marrow transplantation for monogenic inflammatory bowel disease. Issue 1 (25th June 2021) - Morita, Mari; Takeuchi, Ichiro; Kato, Motohiro; Migita, Ohsuke; Jimbo, Keisuke; Shimizu, Hirotaka; Yoshimura, Satoshi; Tomizawa, Daisuke; Shimizu, Toshiaki; Hata, Kenichiro; Ishiguro, Akira; Arai, Katsuhiro
Abstract: Background: Some monogenic inflammatory bowel diseases (IBDs) are known to be refractory to conventional treatments. Although allogeneic hematopoietic stem‐cell transplantation (allo‐HSCT) has become a curative therapeutic option for certain monogenic IBDs, its effectiveness regarding endoscopic improvements has not been clarified. Methods: The clinical course and endoscopic findings of patients with monogenic IBDs who were treated with allo‐HSCT between December 2017 and November 2018 at the National Center for Child Health and Development, were retrospectively reviewed. The clinical disease activity was assessed using the weighted Pediatric Crohn's Disease Activity Index (wPCDAI) and the endoscopic finding was evaluated using the Simple Endoscopic Score for Crohn's Disease (SES‐CD). Clinical remission was defined as a wPCDAI <10 and endoscopic remission was defined as an SES‐CD of 2 or less. Results: Four patients with severe monogenic IBDs, including three with X‐linked inhibitors of apoptosis protein (XIAP) deficiency and one with interleukin‐10 signaling defect, were treated with allo‐HSCT with reduced‐intensity conditioning. In four patients, the maximum scores of wPCDAI and SES‐CD before allo‐HSCT ranged from 67.5 to 120 and 20 to 34, respectively. After allo‐HSCT, all four patients showed a significant improvement in intestinal inflammation and achieved both clinical and endoscopic remission. Although patients with XIAP deficiency presented with post‐transplant hemophagocytic lymphohistiocytosis and a relatively late engraftment, all patients achieved prolonged clinical remission, and IBD medications were successfully discontinued in all patients. Conclusion: Allo‐HSCT for monogenic IBD resulted in complete clinical resolution with endoscopically confirmed mucosal healing.